Respuesta :

Answer:

[tex] \dfrac{df^{1}(16)}{dx} = \pm \dfrac{1}{10} [/tex]

Step-by-step explanation:

[tex] f(x) = x^2 + 4x - 5 [/tex]

First we find the inverse function.

[tex] y = x^2 + 4x - 5 [/tex]

[tex] x = y^2 + 4y - 5 [/tex]

[tex] y^2 + 4y - 5 = x [/tex]

[tex] y^2 + 4y = x + 5 [/tex]

[tex] y^2 + 4y + 4 = x + 5 + 4 [/tex]

[tex] (y + 2)^2 = x + 9 [/tex]

[tex] y + 2 = \pm\sqrt{x + 9} [/tex]

[tex] y = -2 \pm\sqrt{x + 9} [/tex]

[tex]f^{-1}(x) = -2 \pm\sqrt{x + 9}[/tex]

[tex]f^{-1}(x) = -2 \pm (x + 9)^{\frac{1}{2}}[/tex]

Now we find the derivative of the inverse function.

[tex]\dfrac{df^{-1}(x)}{dx} = \pm \dfrac{1}{2}(x + 9)^{-\frac{1}{2}}[/tex]

[tex]\dfrac{df^{-1}(x)}{dx} = \pm \dfrac{1}{2\sqrt{x + 9}}[/tex]

Now we evaluate the derivative of the inverse function at x = 16.

[tex]\dfrac{df^{-1}(16)}{dx} = \pm \dfrac{1}{2\sqrt{16 + 9}}[/tex]

[tex]\dfrac{df^{-1}(16)}{dx} = \pm \dfrac{1}{2\sqrt{25}}[/tex]

[tex]\dfrac{df^{-1}(16)}{dx} = \pm \dfrac{1}{2 \times 5 }[/tex]

[tex]\dfrac{df^{-1}(16)}{dx} = \pm \dfrac{1}{10}[/tex]

ACCESS MORE